How Can Local Governments Address Pandemic Inequities? - Deslatte, Aaron (Public Adm Rev, 2020)
COVID‐19 is exposing a nexus between communities disproportionately suffering from underlying health conditions, policy‐reinforced disparities, and susceptibility to the disease. As the virus spreads, policy responses will need to shift from focusing on surveillance and mitigation to recovery and prevention. Local governments, with their histories of mutual aid and familiarity with local communities, are capable of meeting these challenges. However, funding must flow in a flexible enough fashion for local governments to tailor their efforts to preserve vital services and rebuild local economies. The authors argue that the Community Development Block Grant and the Energy Efficiency and Conservation Block Grant programs are mechanisms for providing funds in a manner that is adaptable to local context while also focusing on increasing social equity. Administrators must emphasize the fourth pillar of public administration—social equity—in framing government responses to the pandemic.